Стан мікроциркуляції у хворих на гіпотиреоз - Зелінська, Н. Б. (Clinical Endocrinology and Endocrine Surgery, 2008)
In the article the results of research of microhemocirculation (MHC) by the biomicroscopy of conjunctiva at hypothyroid patients of different age, duration of disease, hard degree and thyroid compensation (euthyroidism or not). The signs of MHC disorders of different localization (vessels in itself, into and out of vessels) was certain. The changes were more expressed at the venules. More frequent the pathological changes of MHC exposed for patients more than 40 years old and with duration of disease over 3 years, rarer the signs of MHC disorders was certain at patients under the 25 years old. A decline of arteriolovenules coefficient was the most sensible index of violations of MHC, including at patients of any age. The euthyroidism does not provide complete normalization of MHC.